Presynaptic roles of intracellular Ca2+ stores in signalling and exocytosis. (22nd March 2010) - Nizami, Sohaib; Lee, Vivian W.Y.; Davies, Jennifer; Long, Philip; Jovanovic, Jasmina N.; Sihra, Talvinder S.
Abstract : The signalling roles of Ca 2+ ic (intracellular Ca 2+ ) stores are well established in non-neuronal and neuronal cells. In neurons, although Ca 2+ ic stores have been assigned a pivotal role in postsynaptic responses to Gq -coupled receptors, or secondarily to extracellular Ca 2+ influx, the functions of dynamic Ca 2+ ic stores in presynaptic terminals remain to be fully elucidated. In the present paper, we review some of the recent evidence supporting an involvement of Ca 2+ ic in presynaptic function, and discuss loci at which this source of Ca 2+ may impinge. Nerve terminal preparations provide good models for functionally examining putative Ca 2+ ic stores under physiological and pathophysiological stimulation paradigms, using Ca 2+ -dependent activation of resident protein kinases as sensors for fine changes in intracellular Ca 2+ levels. We conclude that intraterminal Ca 2+ ic stores may, directly or indirectly, enhance neurotransmitter release following nerve terminal depolarization and/or G-protein-coupled receptor activation. During conditions that prevail following neuronal ischaemia, increased glutamate release instigated by Ca 2+ ic store activation may thereby contribute to excitotoxicity and eventual synaptopathy.